Answer:
D
Step-by-step explanation:
Compare the original function f(x) = 3x to the modified function g(x) = 3(x-5)+4
In g(x) we are subtracting 5 from x and because it's being done to x it means the shift is horizontal (just like the x-axis is horizontal). To figure out which way the graph shifts make that expression equal to zero and solve:
x-5 = 0
x=5 ----> positive 5 so this means 5 units to the right.
The +4 is being added to the entire function and this means it moves up 4 because it's positive 4.